REVIEW OF THE SECOND EDITION OF THE BOOK THE BEHAVIOR OF COSTS AND THE MANAGEMENT OF THE COMPANY; DE BOTTARO; RODRÍGUEZ JÁUREGUI Y YARDÍN BUENOS AIRES: OSMAR D. BUYATTI; 2019. ISBN 978-987-716-118-2 (Costos y Gestión, 2020)
...